Community-Based Tourism Development in Kerangan Ecotourism Village, South Tangerang City - Fabiola Kalalo; Budi Setiawan (Jurnal Syntax Transformation, 2023)
Community-based tourism development represents a facet of sustainable tourism. Keranggan Tourist Village's diverse potential attractions, facilities, and supportive communities are a prime example of an actively developing tourist village. While Keranggan applies community-based development principles, there is room for enhancement through more effective strategies. This research seeks to analyze the economic, social, and cultural dimensions of Community-Based Tourism (CBT) in the development of Keranggan Tourist Village. Drawing from reputable journals, the literature review method serves as the research approach. Economic indicators focus on implementing green entrepreneurship, while social indicators emphasize enhancing the performance of Pokdarwis. Cultural indicators encompass initiatives such as information exchange between local communities and guests, conducting comparative studies with other tourist villages, and providing tourism-related training for the community.